Analisis Pengeluaran Pemerintah Bidang Pendidikan Dan Kesehatan Terhadap Indeks Pembangunan Manusia (IPM) Pada Kawasan Perbatasan Negara Provinsi Sulawesi Utara - Ferly Christian Kolinug; Patricia steffina mawitjere (Jurnal Ekonomi dan Pembangunan Indonesia, 2023)
The purpose of this study is to analyze the effect of government spending on education and health on the Human Development Index in the border areas of North Sulawesi province in the last eleven years. This study uses secondary data taken from the Central Bureau of Statistics of North Sulawesi and the Directorate General of Financial Balance for the period 2011 – 2021. The analysis used was multiple regression analysis of panel data that combined the data of four districts using a panel data analysis model on the eviews application with data collection of Health, Education and Human Growth Index. Regression testing shows Y = 63.9 + 2.9 X1 + 6.47X2. In the T test, it explains that the Education variable has a significant influence on HDI and the results of the Health variable have a significant influence on HDI, the amount of government spending on education and health can be seen from the R-square of 0.96, meaning that X1 and X2 have a significant influence on Y by 96 percent and the rest by other factors.